Réformer l’éducation pour reconstruire la nation : le Guatemala et la réforme éducative 2005 - Emilie Mendonça (Les Cahiers ALHIM)
The subject of this paper is the contemporary process of reconstruction – rather than simply construction – of the Guatemalan nation-state. The paper focuses on the unifying role played by the education system within the new Guatemalan national project and will show how schools today still contribute to establishing a sense of national identity. Since the 1996 Peace Agreements there has been a redefinition of the Guatemalan national identity, giving it a multi-ethnic and multicultural dimension, and it has been the role of schools to convey that identity. An analysis of the centrepiece of the education reform initiated in 2005 – the CNB with its syllabuses and methods for primary school – will illustrate how important the school system is in the national reconstruction project. This paper will first show what features of the nation school is supposed to teach. In a second part, we will have a look at the new approach to didactics the new ideology entailed. Lastly, we will mention the possible obstacles to the implementation of such a sweeping reform which lacks adequate means and for which people are not totally prepared.